Analysis of the border trade agreement (BTA) between Indonesia and Malaysia after renewal - Agrifin Lokovettor; Hengki; Jennifer Putri; Rian Anwar (Institute Of computer Science (IOCS), 2023)
Indonesia has done a variety of bilateral agreement with Malaysia. An agreement consists of several types such as bilateral and multilateral agreements. Bilateral agreements such as Indonesia and Malaysia on Border Trade Agreement (BTA). Even though sometimes a tension between the state on the boundary, then it needs an update on those agreements, seeing that the need of society and state, change on mechanism on the effort to increase the supervision on the implementation of the BTA. This research uses normative research methods, which attempting to examine the regulations between Indonesia and Malaysia which in this case on Border Trade Agreement. Through studying the regulations or agreements, the author examines the existence and implementation of BTA during the enactment of the bilateral agreement between Indonesia and Malaysia to increase the cooperation on the Economy sector. The implementation of this agreement which is not properly implemented. This can be seen from the cases which ever done such as drugs smuggling. The government of states were focused only on the economic sector while the security sector is still abandoned, therefore there’s several cases of smuggling which made the BTA cannot be implemented properly. To solve the problems which occurs severely on the border area, it could be done through adding a patrol point which in line with the border area topography which is hoped to encourage the supervise of the area could done optimally and create an institution which also could help the Indonesia State Army on supervise the cross-border areas.